2016
DOI: 10.1007/s00894-016-2972-6
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation and acidity characterization of biomass sugars: a first-principles study

Abstract: Deprotonation of biomass sugars is investigated by high-level electronic structure calculations, considering α- and β-anomers as well as all O and C sites. Structural alterations are generally focused on the deprotonated sites. Proton migration or/and ring opening occurs in 15 of 42 deprotonation processes and more frequently for D-fructofuranose than D-glucopyranose conformers. Other regular patterns of structural changes are observed; e.g., deprotonation at anomeric sites often cause larger structural pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…[56] Yang et al reported the calculated acidity values (ΔH acid ) for the conjugated base of αand ß-anomers of D-glucopyranose in the range 341-353 and 342-364 kcal.mol −1 and for the conjugated base of αand ß-anomers of D-fructofuranose in different sites in the range 335-355 and 330-385 kcal.mol −1. [57] The acidity value for the conjugated base of αand ßanomers of D-glucopyranose at different sites calculated in the range 341-353 and 342-364 kcal.mol −1 by Salpin et al [58] Our caclculated acidity value for CH 3 -pentose in the range 346-369 kcal.mol −1 and for aldo-pentose in the range 343-355 kcal.mol −1 are in line with available works. [57,58] Moreover, the acidity of ethanol and 2-propanol are 378.3 and 375.1 (kcal.mol −1 ) in the gas phase, respectively.…”
Section: Acidity In Deoxy-hexose Sugarssupporting
confidence: 82%
See 2 more Smart Citations
“…[56] Yang et al reported the calculated acidity values (ΔH acid ) for the conjugated base of αand ß-anomers of D-glucopyranose in the range 341-353 and 342-364 kcal.mol −1 and for the conjugated base of αand ß-anomers of D-fructofuranose in different sites in the range 335-355 and 330-385 kcal.mol −1. [57] The acidity value for the conjugated base of αand ßanomers of D-glucopyranose at different sites calculated in the range 341-353 and 342-364 kcal.mol −1 by Salpin et al [58] Our caclculated acidity value for CH 3 -pentose in the range 346-369 kcal.mol −1 and for aldo-pentose in the range 343-355 kcal.mol −1 are in line with available works. [57,58] Moreover, the acidity of ethanol and 2-propanol are 378.3 and 375.1 (kcal.mol −1 ) in the gas phase, respectively.…”
Section: Acidity In Deoxy-hexose Sugarssupporting
confidence: 82%
“…[57] The acidity value for the conjugated base of αand ßanomers of D-glucopyranose at different sites calculated in the range 341-353 and 342-364 kcal.mol −1 by Salpin et al [58] Our caclculated acidity value for CH 3 -pentose in the range 346-369 kcal.mol −1 and for aldo-pentose in the range 343-355 kcal.mol −1 are in line with available works. [57,58] Moreover, the acidity of ethanol and 2-propanol are 378.3 and 375.1 (kcal.mol −1 ) in the gas phase, respectively. [59] In comparison with these alcohols, the acidity values of methyl-pentose and aldo-pentose sugars are 346-369 and 343-355 kcal.mol −1 ( Table 2); these results suggest the role of H-bonds in increasing the acidity of deoxy-hexose sugars.…”
Section: Acidity In Deoxy-hexose Sugarssupporting
confidence: 82%
See 1 more Smart Citation
“…[16] Consequently,t he number of deprotonated forms to be considered in the negative modei st oo high to perform chemical dynamics simulations, so we decided to work in the positive-ion mode. However,i nt his case chemical derivatization was mandatory for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the predicted acidity values of cyclic glucose and O‐Glc with other sugars is given in Table 1. Yang et al [ 64 ] reported that the calculated acidity values for α‐ and ß‐anomers of D‐glucopyranose range 341–371 and 342–364 kcal.mol −1 , respectively. Salpin et al [ 63 ] predicated the acidity value for α‐ and ß‐anomers of D‐glucopyranose to be in 342–351 and 344–352 kcal.mol −1 range, respectively.…”
Section: Resultsmentioning
confidence: 99%